Estimating the Reliability Function for Transmuted Pareto Distribution Using Simulation - Hasan, Masa Mohammed; Salih, Makki A. Mohammed (Iraqi Journal of Science, 2022)
In this work, the methods (Moments, Modified Moments, L-Moments, Percentile, Rank Set sampling and Maximum Likelihood) were used to estimate the reliability function and the two parameters of the Transmuted Pareto (TP) distribution. We use simulation to generate the required data from three cases this indicates sample size , and it replicates for the real value for parameters, for reliability times values we take . Results were compared by using mean square error (MSE), the result appears as follows : The best methods are Modified Moments, Maximum likelihood and L-Moments in first case, second case and third case respectively.